A. -3 (19) = -3(20) -3 (-1)

B.-3 (19) = (-3)(20) +(-3)(1)

C.-3 (19) = (-3)(20) + (-3) (-1)

D. -3 (19) = (-3)(10) + (-3) (9)

A. -3 (19) = -3(20) -3 (-1)

B.-3 (19) = (-3)(20) +(-3)(1)

C.-3 (19) = (-3)(20) + (-3) (-1)

D. -3 (19) = (-3)(10) + (-3) (9)

Tutors, please sign in to answer this question.

Saugus, MA

19=20 +(-1) or 19=10+9

19 does NOT equal 20+1

therefore B is not a correct use of the distributive property

Oconomowoc, WI

Marion,

if you remember the distributive property is easy to remember if you think

which can be written as

If you take your all your equations it looks like you are trying to show distributive property using **-3(19)**

well in this case our **a** is ** -3**

but we don't have our **b **or **c**

or do we

in A. you have the eqn -3(10) = -3(20) - 3(-1)

if we assume that **20 ** is **b** and **-1** is **c**

then we would have -3(20 + (-1)) = -3(20) - 3(-1) and (20+(-1)) = 19

so A would be a correct usage of the distributive property

in B. you have (-3)(20) + (-3)(1) = -3(20+1) but 20 + 1 ≠ 19

so it wouldn't be a correct usage of the distributive property

for C and D you would need to do the same as I did above

Hope this helps

F

BTW you can find more examples for this property and others at Purple Math

- Algebra 1 4369
- Math 11240
- Algebra 5450
- The Distributive Property 8
- Simplifying Expressions 139
- Equations 758
- Expressions 144
- Gcf 21
- Parentheses 7
- Distributive 3